FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT APARAT DESA UNTUK MELAKUKAN WHISTLEBLOWING (Studi Empiris Aparat Desa di Kecamatan Kelayang, Kabupaten Indragiri Hulu) - Riarni Ferty; Basri Mutia Yesi; Nurazlina Nurazlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The level of deception (fraud) in Indonesia which is still a great deal andrampant corruption is occurring. One of the most effective ways to dismantle the fraudaccording to the ACFE (Association of Certified Fraud Exammer) in the report of theRTTN (Report to the Nation) is a whistleblowing (tips). This research aims to know theinfluence of organizational commitment, machiavellian, reward, idealism ethicalorientation, relativism ethical orientation against interest to do whistleblowing. Thepopulation in this research is the entire apparatus of the village who worked in districtKelayang, Indragiri Hulu Regency. There are 16 villages in Kecamatan Kelayang,Kabupaten Indragiri Hulu. As for the sampling technique used was sampling insindental.Insindental is the determination of the sampling sample based on coincidence, i.e.,anyone who by chance/insindental met with researchers then can be used as a sample, ifa person is seen incidentally found it suitable as a data source. The results of hypothesistesting that is: first, a commitment to the Organization's effect on interest to do thewhistleblowing. Second, machiavellian has no effect against the interest to do thewhistleblowing. Third, reward has no effect against the interest to do the whistleblowing.Fourth, idealism ethical orientation effect on interest to do the whistleblowing. Fifth,relativism ethical orientation has no effect against the interest to do the whistleblowing.Key words: Whistleblowing, Organizational Commitment, Machiavellian, Reward,Idealism Ethical Orientation and Relativism Ethical Orientation